Probability analysis of hepatocellular carcinoma in hepatitis patients in the gray zone - Zhang, Jianna; Yu, Sijie; Zhu, Kailu; Li, Shibo; Huang, Yu (Frontiers in Medicine, 2024)
ObjectiveTo investigate the probability of hepatocellular carcinoma (HCC) in a large number of gray-zone (GZ) patients with chronic hepatitis B (CHB) in clinical practice.MethodsThe patients with CHB who were diagnosed and treated in our hospital from January 2013 to January 2023 were analyzed retrospectively.ResultsAccording to the different levels of HBeAg, ALT and HBV DNA, GZ patients were divided into four categories: (1) Gray zone A (GZ-A): HBeAg positive, normal ALT level, HBV DNA ≤ 106 IU/ml; (2) Gray zone B (GZ-B): HBeAg positive, ALT>ULN, HBV DNA ≤ 2 × 104 IU/ml; (3) Gray zone C (GZ-C): HBeAg negative, normal ALT level, HBV DNA ≥ 2 × 103 IU/ml; and (4) Gray zone D (GZ-D): HBeAg negative, ALT > ULN, serum HBV DNA ≤ 2 × 103 IU/ml. This observational study showed that after adjustment using inverse probability of treatment weighting (IPTW), the probability of developing HCC in the GZ group was similar to that in the immune-tolerant, HBeAg-positive immune active, and inactive groups. The IPTW-adjusted analysis revealed that the probability of developing HCC in the GZ-B subgroup was similar to that in the immune-active and HBeAg-negative immune-active groups.ConclusionThe GZ group and GZ-B subgroup have a higher risk of HCC. Anti-hepatitis B virus therapy should be considered as early as possible for patients in the GZ group, especially in the GZ-B subgroup.